A phase change ceramicized foamed silica gel composite fireproof sheet and a preparation method thereof

By introducing modified phase change microcapsules and ceramic composite particles into ceramicized foamed silicone rubber, the problems of insufficient heat absorption and interfacial bonding performance of existing materials in the early stage of thermal runaway are solved, realizing the synergistic effect of phase change thermal storage and high-temperature ceramicized protection, and improving the long-term service stability and fire resistance of the material.

CN123026918APending Publication Date: 2026-11-03奥创特新(南通)新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611462020.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing ceramicized foamed silicone rubber materials cannot quickly absorb a large amount of heat in the early stages of thermal runaway, making it difficult to effectively reduce local temperature rise and suppress heat diffusion to surrounding cells. At the same time, the interfacial bonding performance between traditional ceramicized fillers and silicone rubber matrix is ​​insufficient, affecting the long-term service stability of the material. Furthermore, the encapsulation stability and interfacial compatibility of phase change materials are poor.

Method used

By reacting melamine polyphosphate with formaldehyde to form a phosphorus-containing prepolymer, coating a phase change material and modifying it with siloxane hybridization, and combining it with aluminum hydroxide and zinc borate to prepare modified ceramic composite particles, which are then mixed with components such as vinyl silicone oil, foamed and vulcanized to form a phase change ceramic foamed silicone composite fireproof sheet.

Benefits of technology

It improves the encapsulation stability and interfacial bonding performance of phase change materials, enabling them to absorb heat at low temperatures and form a dense ceramic protective layer at high temperatures, thus synergistically achieving phase change heat storage and high-temperature ceramic protection, and improving the structural stability and fire resistance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of phase change ceramicized foamed silica gel composite fireproof sheet and preparation method thereof, and it relates to the technical field of polymer composite material.The melamine polyphosphate, melamine and formaldehyde are reacted to obtain phosphorus-containing prepolymer, and in-situ coated paraffin to obtain phase change microcapsule;Silica ethyl ester, KH570 are reacted by sol-gel to form siloxane hybrid layer on the surface of phase change microcapsule, and modified phase change microcapsule is prepared;Aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution are reacted to obtain composite particles, and modified ceramic composite particles are obtained by silane coupling agent modification;Vinyl silicone oil, high hydrogen-containing silicone oil, 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles and modified phase change microcapsule are mixed to obtain phase change ceramicized foamed silica gel composite fireproof sheet.The composite fireproof sheet prepared by the application has phase change heat storage performance and high temperature ceramic protection performance, and can maintain certain structural integrity after single-side flame burning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, specifically to a phase change ceramicized foamed silicone composite fireproof sheet and its preparation method. Background Technology

[0002] With the rapid development of new energy vehicles, energy storage power stations, and aviation lithium battery equipment, the combustion, explosion, and thermal runaway issues of lithium-ion batteries have attracted widespread attention. Existing thermal safety protection materials for power batteries mainly employ ceramic fibers, aerogels, flame-retardant polymer composites, and ceramicized silicone rubber. Among these, foamed silicone rubber materials possess advantages such as light weight, good flexibility, high temperature resistance, and excellent buffering performance, meeting the protection requirements of complex battery module assembly environments. However, existing ceramicized foamed silicone rubber primarily relies on its own low thermal conductivity and the inorganic ceramic layer formed at high temperatures for passive thermal insulation. In the early stages of thermal runaway, it cannot quickly absorb large amounts of heat, making it difficult to effectively reduce local temperature rise and inhibit heat diffusion to surrounding cells. Simultaneously, the interfacial bonding performance between traditional ceramicized fillers and the silicone rubber matrix is ​​insufficient, easily leading to uneven filler dispersion and structural defects in the high-temperature ceramic layer, affecting the long-term service stability of the material.

[0003] Phase change materials (PCMs) can absorb heat through solid-liquid phase change processes, showing promising applications in thermal management. However, paraffin-based PCMs suffer from problems such as melt leakage, low thermal conductivity, and poor compatibility with polymer matrices, limiting their application in fire-resistant and heat-insulating materials. Existing PCM microcapsules typically only utilize the shell layer to improve the encapsulation stability of PCMs, making it difficult to further participate in the high-temperature ceramicization protection process. Therefore, there is an urgent need to develop a foamed silicone composite fire-resistant material that can combine phase change heat absorption at low temperatures and ceramicization protection at medium and high temperatures, while also possessing good interfacial bonding performance and structural stability, to meet the demand for high-efficiency thermal safety protection materials in fields such as power battery modules, energy storage batteries, and aerospace lithium battery equipment. Summary of the Invention

[0004] The purpose of this invention is to provide a phase change ceramicized foamed silicone composite fireproof sheet and its preparation method, so as to solve the problems existing in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Melamine polyphosphate, melamine and formaldehyde are reacted to form a phosphorus-containing prepolymer, and the phosphorus-containing prepolymer is used to coat the phase change material to obtain phase change microcapsules; (2) The phase change microcapsules are modified by siloxane hybridization to form a siloxane hybrid layer on their surface, thereby obtaining modified phase change microcapsules; (3) Aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution are mixed and reacted to obtain composite particles; the composite particles are surface modified with KH570 to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen-containing silicone oil and ethynylcyclohexanol to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, the modified ceramic composite particles and the modified phase change microcapsules to obtain component B; mix component A and component B, add platinum catalyst, and foam vulcanize to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0006] Furthermore, the phase change material in step (1) is paraffin wax.

[0007] Furthermore, the preparation method of the phase change microcapsules includes: Melamine polyphosphate, melamine, formaldehyde solution with a mass concentration of 37-40% and deionized water are mixed in a mass ratio of 1:(6-8):(6-10):(12-16), and triethanolamine is added to adjust the pH to 8-8.5. The mixture is reacted at 60-80℃ for 1-2 hours to obtain a phosphorus-containing prepolymer. Deionized water, paraffin wax, and sodium dodecylbenzenesulfonate were mixed at a mass ratio of 1:(0.2~0.5):(0.002~0.01) and stirred at 60~70℃ and 800~1500 r / min for 2~5 h to obtain an oil-in-water emulsion. A phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate over 0.5~1 h, and the mixture was reacted at 60~70℃ for 2~4 h to obtain phase change microcapsules. The mass ratio of the phosphorus-containing prepolymer to the oil-in-water emulsion was 1:(3~6).

[0008] Furthermore, the method for preparing the modified phase change microcapsules in step (2) includes: Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:(2~2.5), and the pH was adjusted to 9 with 25~28wt% concentrated ammonia to obtain a mixed solution. Ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:(1.5~2.5):(4~6) to obtain a silane solution. Phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:(0.01~0.02):(2~3), stirred at 35~45℃ for 10~20 min, and then 0.7~1.1 times the mass of the phase change microcapsules of silane solution were added. The mixture was stirred for 3~4 h, aged at room temperature for 10~14 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules.

[0009] Furthermore, the method for preparing the composite particles in step (3) includes: The mixture is prepared by reacting aluminum hydroxide slurry, sodium borate aqueous solution, and zinc sulfate aqueous solution at a mass ratio of 1:(0.4~0.45):(0.6~1) at 85~95℃ for 8~12h.

[0010] Furthermore, the aluminum hydroxide slurry is prepared by mixing aluminum hydroxide and deionized water at a mass ratio of 1:(6.5~7.5) and stirring at 85~95℃ for 1~1.5h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:(5~6) and stirring at 85~95℃ for 1~1.5h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:(6.5~7.5) and stirring at 85~95℃ for 1~1.5h; and the average particle size of the aluminum hydroxide is 1~5μm.

[0011] Furthermore, the modified ceramic composite particles are surface modified using KH570, and the specific method is as follows: KH570, ethanol, and deionized water were mixed at a mass ratio of 1:(8~10):(1~2), and the pH of the system was adjusted to 3~4 using glacial acetic acid. The mixture was hydrolyzed at 25~30℃ for 0.5~1.5h to obtain a silane hydrolysate. The composite particles were then mixed with the silane hydrolysate at a mass ratio of 1:(6~8) and reacted at 70~80℃ for 1.5~2.5h. After washing and vacuum drying, the modified ceramic composite particles were obtained.

[0012] Furthermore, in step (4), the mass ratio of vinyl silicone oil, high-hydrogen silicone oil, and ethynylcyclohexanol in component A is 1:(0.2~0.3):(0.01~0.02); and the mass ratio of 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in component B is 1:(0.4~0.6):(1.2~1.6):(0.5~0.9). The vinyl silicone oil has a vinyl content of 0.45%, the high-hydrogen silicone oil has a hydrogen content of 1.4%, the hydroxyl silicone oil has a hydroxyl content of 3.6%, the 107 room temperature vulcanized methyl silicone rubber has a hydroxyl content of >8%, and a viscosity of 50,000 mPa·s at 25°C.

[0013] Furthermore, component A and component B are mixed at a mass ratio of 1:(1.2~1.6), and a platinum catalyst accounting for 1~1.5% of the total mass of components A and B is added. The mixture is stirred for 10~30s at 25~30℃ and 800~1500r / min, poured into a polytetrafluoroethylene mold, allowed to stand for 2~3min, and then cured at 50~55℃ for 12~20h to obtain a phase change ceramicized foamed silicone composite fireproof sheet. The platinum catalyst is a Karstedt catalyst with a platinum content of 3000ppm, manufactured by Shanghai Beyotime Biotechnology Co., Ltd.

[0014] The present invention also discloses a phase change ceramicized foamed silicone composite fireproof sheet prepared by the preparation method of the phase change ceramicized foamed silicone composite fireproof sheet as described above.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) In this invention, melamine polyphosphate is introduced into the phosphorus-containing amino resin shell of phase change microcapsules. The phosphorus-containing amino resin structure is formed by melamine polyphosphate, melamine and formaldehyde, and the paraffin phase change material is encapsulated. The ceramicization promoting component is no longer added directly to the silicone rubber matrix in the form of free filler, but is fixed in the shell of the phase change microcapsule. While improving the encapsulation stability of the phase change material, the phosphorus-containing functional component is uniformly dispersed in the composite material, avoiding the problems of poor compatibility and easy agglomeration of traditional ceramicization promoters with silicone rubber matrix.

[0016] (2) In this invention, the phase change microcapsules are further modified by sol-gel using ethyl silicate and KH570 to form a siloxane hybrid protective layer outside the phosphorus-containing shell. This double-layer structure is beneficial to improving the encapsulation stability of the phase change material and improving the interfacial bonding performance between the phase change microcapsules and the silicone rubber matrix, thereby improving the structural stability of the composite fireproof sheet during long-term use.

[0017] (3) By combining zinc borate and aluminum hydroxide, the present invention constructs surface-loaded ceramic composite particles, which is beneficial to make boron-containing and zinc-containing components form a tight composite with aluminum hydroxide. During the high-temperature ceramicization process, the zinc borate composite structure can promote the liquid phase mass transfer and sintering process between inorganic components, improve the ceramicization reaction efficiency, and promote the formation of a denser and more continuous ceramic protective layer, thereby improving the problem of excessive pores and insufficient structural integrity in the process of traditional ceramic fillers forming ceramic layers.

[0018] (4) This invention introduces modified phase change microcapsules and ceramicized composite particles into a foamed silicone rubber system to achieve synergistic construction of functional components. In the initial stage of thermal shock, paraffin undergoes a phase change and absorbs heat; as the temperature further increases, the polyphosphate component in the phosphorus-containing phase change microcapsules releases phosphorus-containing active species, which, together with the alumina component generated by the pyrolysis of aluminum hydroxide and the silicon-containing inorganic phase formed by the pyrolysis of silicone rubber, promote the formation of a ceramicized protective structure. This is beneficial for maintaining the structural integrity of the material under flame burning conditions, and achieves the synergistic effect of phase change heat storage and high-temperature ceramicized protection. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] To more clearly illustrate the method provided by the present invention, the following embodiments will be described in detail.

[0021] Example 1: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet, comprising the following steps: (1) Melamine polyphosphate, melamine, 37wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:6:6:12. Triethanolamine was added until the pH value was adjusted to 8. The mixture was stirred at 60℃ for 1h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.2:0.002. The mixture was stirred at 60℃ and 800r / min for 2h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:3. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate over 0.5h. The mixture was reacted at 60℃ for 2h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2, and the pH was adjusted to 9 with 25wt% concentrated ammonia to obtain a mixed solution; ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:1.5:4 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.01:2, stirred at 35℃ for 10 min, and 0.7 times the mass of the phase change microcapsules of silane solution were added. The mixture was stirred for 3 h, aged at room temperature for 10 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution in a mass ratio of 1:0.4:0.6. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 85℃ for 10 min, add zinc sulfate aqueous solution, stir for 8 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water in a mass ratio of 1:8:1, adjust the pH of the solution to 3 with glacial acetic acid, stir at 25℃ for 0.5 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate in a mass ratio of 1:6, stir at 70℃ for 1.5 h, filter, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.2:0.01 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in a mass ratio of 1:0.4:1.2:0.5 to obtain component B; mix components A and B in a mass ratio of 1:1.2, add 1% of the total mass of components A and B of Karstedt catalyst, stir at 25°C and 800 r / min for 10 s, pour into a polytetrafluoroethylene mold and let stand for 2 min, then cure at 50°C for 12 h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0022] The aluminum hydroxide slurry in step (3) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:6.5 and stirring at 85°C for 1 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:5 and stirring at 85°C for 1 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:6.5 and stirring at 85°C for 1 h.

[0023] Example 2: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet, comprising the following steps: (1) Melamine polyphosphate, melamine, 39wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:7:8:14. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 70℃ for 1.5h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.35:0.006. The mixture was stirred at 65℃ and 1100r / min for 3.5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:4.5. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 65℃ for 3h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2.5, and the pH was adjusted to 9 with 28wt% concentrated ammonia to obtain a mixed solution; ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:2:5 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.015:2.5, stirred at 40℃ for 15 min, and 0.9 times the mass of the phase change microcapsules of silane solution were added, stirred for 3.5 h, aged at room temperature for 12 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution in a mass ratio of 1:0.43:0.8. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 90℃ for 15 min, add zinc sulfate aqueous solution, stir for 10 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water in a mass ratio of 1:9:1.5, adjust the pH of the solution to 3.5 with glacial acetic acid, stir at 27℃ for 1 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate in a mass ratio of 1:7, stir at 75℃ for 2 h, filter, wash with anhydrous ethanol, and vacuum dry at 85℃ to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in a mass ratio of 1:0.5:1.4:0.7 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27℃ and 1100r / min for 20s, pour into a polytetrafluoroethylene mold and let stand for 2.5min, then cure at 55℃ for 16h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0024] The aluminum hydroxide slurry in step (3) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:5.5 and stirring at 90°C for 1.5 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h.

[0025] Example 3: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet, comprising the following steps: (1) Melamine polyphosphate, melamine, 40wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:8:10:16. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 80℃ for 2h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.5:0.01. The mixture was stirred at 70℃ and 1500r / min for 5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:6. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 70℃ for 4h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2.5, and the pH was adjusted to 9 with 28wt% concentrated ammonia to obtain a mixed solution; ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:2.5:6 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.02:3, stirred at 45℃ for 20 min, and then 1.1 times the mass of the phase change microcapsules of silane solution were added. The mixture was stirred for 4 h, aged at room temperature for 14 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution at a mass ratio of 1:0.45:1. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 95℃ for 15 min, add zinc sulfate aqueous solution, stir for 12 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water at a mass ratio of 1:10:2, adjust the pH of the solution to 4 with glacial acetic acid, stir at 30℃ for 1.5 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate at a mass ratio of 1:8, stir at 80℃ for 2.5 h, filter, wash with anhydrous ethanol, and vacuum dry at 90℃ to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.3:0.02 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in a mass ratio of 1:0.6:1.6:0.9 to obtain component B; mix components A and B in a mass ratio of 1:1.6, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 30℃ and 1500r / min for 30s, pour into a polytetrafluoroethylene mold and let stand for 3min, then cure at 55℃ for 20h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0026] The aluminum hydroxide slurry in step (3) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:7.5 and stirring at 95°C for 1.5 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:6 and stirring at 95°C for 1.5 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:7.5 and stirring at 95°C for 1.5 h.

[0027] Comparative Example 1: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Melamine polyphosphate, melamine, 39wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:7:8:14. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 70℃ for 1.5h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.35:0.006. The mixture was stirred at 65℃ and 1100r / min for 3.5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:4.5. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 65℃ for 3h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2.5, and the pH was adjusted to 9 with 28wt% concentrated ammonia to obtain a mixed solution; ethyl silicate and anhydrous ethanol were mixed at a mass ratio of 1:5 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.015:2.5, stirred at 40℃ for 15 min, and 0.9 times the mass of the phase change microcapsules of silane solution were added. The mixture was stirred for 3.5 h, aged at room temperature for 12 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution in a mass ratio of 1:0.43:0.8. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 90℃ for 15 min, add zinc sulfate aqueous solution, stir for 10 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water in a mass ratio of 1:9:1.5, adjust the pH of the solution to 3.5 with glacial acetic acid, stir at 27℃ for 1 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate in a mass ratio of 1:7, stir at 75℃ for 2 h, filter, wash with anhydrous ethanol, and vacuum dry at 85℃ to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in a mass ratio of 1:0.5:1.4:0.7 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27℃ and 1100r / min for 20s, pour into a polytetrafluoroethylene mold and let stand for 2.5min, then cure at 55℃ for 16h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0028] The aluminum hydroxide slurry in step (3) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:5.5 and stirring at 90°C for 1.5 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h.

[0029] Comparative Example 2: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Melamine polyphosphate, melamine, 39wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:7:8:14. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 70℃ for 1.5h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.35:0.006. The mixture was stirred at 65℃ and 1100r / min for 3.5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:4.5. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 65℃ for 3h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution in a mass ratio of 1:0.43:0.8. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 90℃ for 15 min, add zinc sulfate aqueous solution, stir for 10 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water in a mass ratio of 1:9:1.5, adjust the pH of the solution to 3.5 with glacial acetic acid, stir at 27℃ for 1 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate in a mass ratio of 1:7, stir at 75℃ for 2 h, filter, wash with anhydrous ethanol, and vacuum dry at 85℃ to obtain modified ceramic composite particles; (3) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and phase change microcapsules in a mass ratio of 1:0.5:1.4:0.7 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27℃ and 1100r / min for 20s, pour into a polytetrafluoroethylene mold and let stand for 2.5min, then cure at 55℃ for 16h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0030] The aluminum hydroxide slurry in step (2) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:5.5 and stirring at 90°C for 1.5 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h.

[0031] Comparative Example 3: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Weigh aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution in a mass ratio of 1:0.43:0.8. Mix aluminum hydroxide slurry and sodium borate aqueous solution, stir at 90℃ for 15 min, add zinc sulfate aqueous solution, stir for 10 h, filter, wash with deionized water at 90℃, wash with anhydrous ethanol, and vacuum dry at 80℃ to obtain composite particles; mix KH570, ethanol and deionized water in a mass ratio of 1:9:1.5, adjust the pH of the solution to 3.5 with glacial acetic acid, stir at 27℃ for 1 h to obtain silane hydrolysate; mix composite particles and silane hydrolysate in a mass ratio of 1:7, stir at 75℃ for 2 h, filter, wash with anhydrous ethanol, and vacuum dry at 85℃ to obtain modified ceramic composite particles; (2) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, and modified ceramic composite particles in a mass ratio of 1:0.5:1.4 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27℃ and 1100r / min for 20s, pour into a polytetrafluoroethylene mold and let stand for 2.5min, then cure at 55℃ for 16h to obtain phase change ceramic foamed silicone composite fireproof sheet.

[0032] The aluminum hydroxide slurry in step (1) is prepared by mixing aluminum hydroxide with an average particle size of 3 μm and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:5.5 and stirring at 90°C for 1.5 h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:7 and stirring at 90°C for 1.5 h.

[0033] Comparative Example 4: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Melamine polyphosphate, melamine, 39wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:7:8:14. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 70℃ for 1.5h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.35:0.006. The mixture was stirred at 65℃ and 1100r / min for 3.5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:4.5. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 65℃ for 3h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2.5, and the pH was adjusted to 9 with 28wt% concentrated ammonia to obtain a mixed solution; ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:2:5 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.015:2.5, stirred at 40℃ for 15 min, and 0.9 times the mass of the phase change microcapsules of silane solution were added, stirred for 3.5 h, aged at room temperature for 12 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) KH570, ethanol and deionized water were mixed in a mass ratio of 1:9:1.5, the pH of the solution was adjusted to 3.5 with glacial acetic acid, and stirred at 27°C for 1 h to obtain silane hydrolysate; aluminum hydroxide with an average particle size of 3 μm was mixed with silane hydrolysate in a mass ratio of 1:7, stirred at 75°C for 2 h, filtered, washed with anhydrous ethanol and dried under vacuum at 85°C to obtain modified aluminum hydroxide; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified aluminum hydroxide, and modified phase change microcapsules in a mass ratio of 1:0.5:1.4:0.7 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27°C and 1100 r / min for 20 s, pour into a polytetrafluoroethylene mold and let stand for 2.5 min, then cure at 55°C for 16 h to obtain phase change ceramicized foamed silicone composite fireproof sheet.

[0034] Comparative Example 5: A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet includes the following steps: (1) Melamine polyphosphate, melamine, 39wt% formaldehyde solution and deionized water were mixed in a mass ratio of 1:7:8:14. Triethanolamine was added until the pH value was adjusted to 8.5. The mixture was stirred at 70℃ for 1.5h to obtain a phosphorus-containing prepolymer. Deionized water, paraffin and sodium dodecylbenzene sulfonate were mixed in a mass ratio of 1:0.35:0.006. The mixture was stirred at 65℃ and 1100r / min for 3.5h to obtain an oil-in-water emulsion. The phosphorus-containing prepolymer and the oil-in-water emulsion were weighed in a mass ratio of 1:4.5. The phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate within 1h. The mixture was reacted at 65℃ for 3h. After filtration, washing and vacuum drying of the filter residue, phase change microcapsules were obtained. (2) Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:2.5, and the pH was adjusted to 9 with 28wt% concentrated ammonia to obtain a mixed solution; ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:2:5 to obtain a silane solution; phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:0.015:2.5, stirred at 40℃ for 15 min, and 0.9 times the mass of the phase change microcapsules of silane solution were added, stirred for 3.5 h, aged at room temperature for 12 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules; (3) KH570, ethanol and deionized water were mixed at a mass ratio of 1:9:1.5, the pH of the solution was adjusted to 3.5 with glacial acetic acid, and stirred at 27°C for 1 h to obtain silane hydrolysate; aluminum hydroxide with an average particle size of 3 μm was mixed with silane hydrolysate at a mass ratio of 1:7, stirred at 75°C for 2 h, filtered, washed with anhydrous ethanol and dried under vacuum at 85°C to obtain modified aluminum hydroxide; (4) Mix vinyl silicone oil, high hydrogen silicone oil, and ethynylcyclohexanol in a mass ratio of 1:0.25:0.015 to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified aluminum hydroxide, zinc borate, and modified phase change microcapsules in a mass ratio of 1:0.5:1.12:0.28:0.7 to obtain component B; mix components A and B in a mass ratio of 1:1.4, add 1.5% of the total mass of components A and B of Karstedt catalyst, stir at 27℃ and 1100r / min for 20s, pour into a polytetrafluoroethylene mold and let stand for 2.5min, then cure at 55℃ for 16h to obtain phase change ceramicized foamed silicone composite fireproof sheet.

[0035] Experimental Example 1: Tensile properties, thermal properties, vitrification properties and fire resistance tests Tensile property test method: The phase change ceramic foamed silicone composite fireproof sheet obtained in each embodiment and the materials of each comparative example were tested for tensile strength and elongation at break according to GB / T528-2009. The tensile rate was 10 mm / min. The sample was made into a dumbbell shape with a length of 115 mm, a width of 4 mm and a thickness of 5 mm.

[0036] Thermal performance testing method: The melting enthalpy and crystallization enthalpy of the phase change ceramicized foamed silicone composite fireproof sheets and the comparative materials obtained in each embodiment were tested using a differential scanning calorimeter under a pure nitrogen atmosphere. The temperature range was 20~80℃, the heating and cooling rates were both 10℃ / min, and the sample mass was 5mg. The DSC heat flow curves of the samples were recorded. The melting enthalpy of the samples was obtained by integrating the peak area of ​​the endothermic peak during the heating stage, and the crystallization enthalpy was obtained by integrating the peak area of ​​the exothermic peak during the cooling stage.

[0037] Vitrification performance test method: The phase change ceramicized foamed silicone composite fireproof sheets obtained in each embodiment and the materials of each comparative example were placed in a muffle furnace for air combustion. The heat treatment temperature was 1000℃, the heating rate was 10℃ / min before 800℃, the heating rate was 5℃ / min from 800℃ to 1000℃, and the temperature was held at 1000℃ for 30min. Then, the residue was obtained by natural cooling to room temperature. The mass loss rate and linear shrinkage rate were calculated.

[0038] Mass loss rate = [(mass before heat treatment - mass after heat treatment) / mass before heat treatment] × 100% Linear shrinkage rate = [(length of sample before heat treatment - length of sample after heat treatment) / length of sample before heat treatment] × 100% Fire resistance performance test method: The phase change ceramicized foamed silicone composite fireproof sheets obtained in each embodiment were fixed on an iron stand. An alcohol torch was used to burn the center of one side of the fireproof sheet. If the sample was not burned through after 15 minutes and there was no open flame on the back, the material met the fire resistance performance requirements. The fireproof sheet thickness was 2mm, the outer flame temperature of the alcohol torch was approximately 1050~1200℃, and the flame height was 90mm.

[0039] The results are shown in Table 1.

[0040] Table 1

[0041] By comparing Example 2 with Comparative Example 1, it can be found that Example 2, which uses ethyl silicate and KH570 to modify the phase change microcapsules, increased the tensile strength and elongation at break from 0.36 MPa and 51.6% to 0.43 MPa and 59.0%, respectively, and reduced the mass loss rate from 33.2% to 31.8%. This indicates that the introduction of KH570 is beneficial to improving the interfacial bonding between the microcapsules and the silicone rubber matrix, and improving the quality retention ability after high-temperature treatment.

[0042] A comparison of Example 2 and Comparative Example 2 reveals that without the outer siloxane hybrid layer, the fireproof sheet exhibits higher enthalpy of melting and crystallization, but lower tensile strength and elongation at break, resulting in a higher mass loss rate. This indicates that while the siloxane hybrid layer increases the proportion of non-phase change components, thus reducing the phase change enthalpy per unit mass of fireproof sheet, it is beneficial for improving the material's mechanical properties and high-temperature mass retention capability.

[0043] By comparing Example 2 with Comparative Example 3, it can be found that after adding modified phase change microcapsules, the melting enthalpy and crystallization enthalpy of the fireproof sheet increased from 0 to 14.0 J / g and 13.7 J / g, respectively, indicating that the modified phase change microcapsules endow the fireproof sheet with phase change heat storage performance.

[0044] A comparison of Example 2 and Comparative Example 4 reveals that after pre-compositing the zinc borate component with aluminum hydroxide, the mass loss rate of the fireproof sheet decreased from 37.2% to 31.8%, and the fireproof performance improved from failing to passing. This indicates that the composite ceramic particles are beneficial for improving the material's quality retention and fireproof performance after high-temperature treatment. The lower linear shrinkage rate of Comparative Example 4 may be related to its lower degree of sintering; this alone cannot be used to conclude that its ceramicization performance is superior.

[0045] A comparison of Example 2 and Comparative Example 5 reveals that in-situ composite of zinc borate onto the surface of aluminum hydroxide allows for uniform liquid-phase sintering at the particle interface; whereas in Comparative Example 5, zinc borate is directly added to the system, leading to localized enrichment and uneven liquid-phase sintering. Therefore, Example 2 exhibits lower mass loss and better fire resistance after firing. Furthermore, the in-situ composite particles are more uniformly dispersed, resulting in superior tensile strength and elongation at break compared to Comparative Example 5.

[0046] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of the invention is defined by the appended technical solutions rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the technical solutions are intended to be included within the present invention.

Claims

1. A method for preparing a phase change ceramicized foamed silicone composite fireproof sheet, characterized in that, Includes the following steps: (1) Melamine polyphosphate, melamine and formaldehyde are reacted to form a phosphorus-containing prepolymer, and the phosphorus-containing prepolymer is used to coat the phase change material to obtain phase change microcapsules; (2) The phase change microcapsules are modified by siloxane hybridization to form a siloxane hybrid layer on their surface, thereby obtaining modified phase change microcapsules; (3) Aluminum hydroxide slurry, sodium borate aqueous solution and zinc sulfate aqueous solution are mixed and reacted to obtain composite particles; the composite particles are surface modified with KH570 to obtain modified ceramic composite particles; (4) Mix vinyl silicone oil, high hydrogen-containing silicone oil and ethynylcyclohexanol to obtain component A; mix 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, the modified ceramic composite particles and the modified phase change microcapsules to obtain component B; mix component A and component B, add platinum catalyst, and foam vulcanize to obtain phase change ceramic foamed silicone composite fireproof sheet.

2. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 1, characterized in that, The phase change material in step (1) is paraffin wax.

3. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 2, characterized in that, The preparation method of the phase change microcapsules includes: Melamine polyphosphate, melamine, formaldehyde solution with a mass concentration of 37-40% and deionized water are mixed in a mass ratio of 1:(6-8):(6-10):(12-16), and triethanolamine is added to adjust the pH to 8-8.

5. The mixture is reacted at 60-80℃ for 1-2 hours to obtain a phosphorus-containing prepolymer. Deionized water, paraffin wax, and sodium dodecylbenzenesulfonate were mixed at a mass ratio of 1:(0.2~0.5):(0.002~0.01) and stirred at 60~70℃ and 800~1500 r / min for 2~5 h to obtain an oil-in-water emulsion. A phosphorus-containing prepolymer was added dropwise to the oil-in-water emulsion at a uniform rate over 0.5~1 h, and the mixture was reacted at 60~70℃ for 2~4 h to obtain phase change microcapsules. The mass ratio of the phosphorus-containing prepolymer to the oil-in-water emulsion was 1:(3~6).

4. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 1, characterized in that, The method for preparing modified phase change microcapsules in step (2) includes: Deionized water and anhydrous ethanol were mixed at a mass ratio of 1:(2~2.5), and the pH was adjusted to 9 with 25~28wt% concentrated ammonia to obtain a mixed solution. Ethyl silicate, KH570 and anhydrous ethanol were mixed at a mass ratio of 1:(1.5~2.5):(4~6) to obtain a silane solution. Phase change microcapsules, sodium dodecylbenzenesulfonate and the mixed solution were mixed at a mass ratio of 1:(0.01~0.02):(2~3), stirred at 35~45℃ for 10~20 min, and then 0.7~1.1 times the mass of the phase change microcapsules of silane solution were added. The mixture was stirred for 3~4 h, aged at room temperature for 10~14 h, and dried at 55℃ for 24 h to obtain modified phase change microcapsules.

5. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 1, characterized in that, The method for preparing the composite particles in step (3) includes: The mixture is prepared by reacting aluminum hydroxide slurry, sodium borate aqueous solution, and zinc sulfate aqueous solution at a mass ratio of 1:(0.4~0.45):(0.6~1) at 85~95℃ for 8~12h.

6. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 5, characterized in that, The aluminum hydroxide slurry is prepared by mixing aluminum hydroxide and deionized water at a mass ratio of 1:(6.5~7.5) and stirring at 85~95℃ for 1~1.5h; the sodium borate aqueous solution is prepared by mixing sodium tetraborate decahydrate and deionized water at a mass ratio of 1:(5~6) and stirring at 85~95℃ for 1~1.5h; the zinc sulfate aqueous solution is prepared by mixing zinc sulfate heptahydrate and deionized water at a mass ratio of 1:(6.5~7.5) and stirring at 85~95℃ for 1~1.5h; the average particle size of the aluminum hydroxide is 1~5μm.

7. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 5, characterized in that, The modified ceramic composite particles were surface modified using KH570, and the specific method is as follows: KH570, ethanol, and deionized water were mixed at a mass ratio of 1:(8~10):(1~2), and the pH of the system was adjusted to 3~4 using glacial acetic acid. The mixture was hydrolyzed at 25~30℃ for 0.5~1.5h to obtain a silane hydrolysate. The composite particles were then mixed with the silane hydrolysate at a mass ratio of 1:(6~8) and reacted at 70~80℃ for 1.5~2.5h. After washing and vacuum drying, the modified ceramic composite particles were obtained.

8. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 1, characterized in that, In step (4), the mass ratio of vinyl silicone oil, high-hydrogen silicone oil, and ethynylcyclohexanol in component A is 1:(0.2~0.3):(0.01~0.02); the mass ratio of 107 room temperature vulcanized methyl silicone rubber, hydroxyl silicone oil, modified ceramic composite particles, and modified phase change microcapsules in component B is 1:(0.4~0.6):(1.2~1.6):(0.5~0.9). The vinyl silicone oil has a vinyl content of 0.45%; the high-hydrogen silicone oil has a hydrogen content of 1.4%; the hydroxyl silicone oil has a hydroxyl content of 3.6%; the 107 room temperature vulcanized methyl silicone rubber has a hydroxyl content >8% and a viscosity of 50,000 mPa·s at 25°C.

9. The method for preparing the phase change ceramicized foamed silicone composite fireproof sheet according to claim 8, characterized in that, Component A and component B are mixed at a mass ratio of 1:(1.2~1.6), and a platinum catalyst accounting for 1~1.5% of the total mass of components A and B is added. The mixture is stirred for 10~30s at 25~30℃ and 800~1500r / min, poured into a polytetrafluoroethylene mold, allowed to stand for 2~3min, and then cured at 50~55℃ for 12~20h to obtain a phase change ceramicized foamed silicone composite fireproof sheet. The platinum catalyst is a Karstedt catalyst with a platinum content of 3000ppm.

10. A phase change ceramicized foamed silicone composite fireproof sheet prepared by the preparation method of the phase change ceramicized foamed silicone composite fireproof sheet as described in any one of claims 1 to 9.